Research on the efficiency of green development of industry in Chinese prefecture-level oil and gas cities based on super-efficient SBM-DEA model and Malmquist index - Fei, Sun; Chongliang, Sun; Jie, Luo; Yana, An; Haiyan, Sun (Frontiers in Earth Science, 2023)
With the proposal of Industrial Green Development Plan (2016-2020), it is particularly urgent to focus on the industrial green development of oil and gas cities, actively promote industrial energy efficiency, reduce pollution emissions, and measure the efficiency of their industrial green development. Based on the actual situation of oil and gas cities, we apply the Super-SBM model to measure the industrial green development efficiency of oil and gas cities in 15 years from 2004-2018, analyze the spatial and temporal evolution trends and characteristics of industrial green development efficiency, and also calculate the Malmquist index to dynamically analyze the industrial green development efficiency of oil and gas cities. The results show that the industrial green development efficiency of oil and gas cities as a whole is not high from 2004 to 2018, showing a gentle "W" type fluctuation change. From the spatial dimension, there are significant differences in industrial green development efficiency among oil and gas cities in the east, central and west, with the efficiency value is relatively higher in the west. The total factor productivity of industrial green development is most influenced by the changes of technical efficiency and technological progress. In view of the above problems, it is recommended to broaden green technology innovation channels, increase green technology innovation investment, build a new mechanism for regional synergistic development, and formulate regional graded development strategies.